A dangerous boomerang: Injunctive norms, hostile sexist attitudes, and male‐to‐female sexual aggression. Issue 6 (14th July 2015) - Bosson, Jennifer K.; Parrott, Dominic J.; Swan, Suzanne C.; Kuchynka, Sophie L.; Schramm, Andrew T.
<x xml:space="preserve">Abstract</x> This study examined the interactive effects of injunctive norm exposure and hostile and benevolent sexist attitudes on men's sexually aggressive responses during a behavioral analogue paradigm in which they interacted online with a bogus female partner. Heterosexual adult men (n = 201), recruited from an online sample, read fictional information regarding other men's approval of misogynistic, paternalistic, or egalitarian treatment of women, or non‐gender‐relevant control information. Through a media preference survey, men then learned that their female partner disliked sexual content in films, after which they had an opportunity to send her up to 120 sec' worth of either a sexually explicit or nonsexual film clip. Validating the online sexual aggression paradigm, men with a 1‐year history of sexual assault exhibited more sexually aggressive responding during the film selection paradigm. Moreover, exposure to injunctive norm information produced a boomerang effect, such that men high in hostile sexist attitudes showed an increase in sexual aggression when confronted with paternalism and gender equality norms. Conversely, exposure to paternalism and gender equality norms suppressed the otherwise protective function of high benevolent sexism in reducing men's sexually aggressive tendencies. The implications of these results for social norms interventions are discussed. Aggr. Behav. 41:580–593, 2015. © 2015 Wiley Periodicals, Inc.